Interactions between circulating inflammatory factors and autism spectrum disorder - Rahmah Ashar Sakrani,; Rana Zargham Asif,; Syed Ali Wijdan, (Journal of the Pakistan Medical Association, 2025)
Autism Spectrum Disorder (ASD) is a developmental condition characterised by challenges in social interaction, communication, and repetitive behaviours. Its prevalence has risen in recent years, affecting approximately 1 in 36 children.[1] Recent studies indicate various factors contributing to this disorder, which require further investigation due to the lack of reliable sources for its prevalence in Pakistan. Inflammation is the immune system's defence mechanism in response to harmful stimuli including pathogens, damaged cells, and several toxic compounds. Chronic inflammation plays a critical role in the pathophysiology of ASD via neuroinflammation, including microglial activation and astrocyte dysfunction. Microglia, the primary immune cells in the brain, are activated in ASD, indicating chronic neuroinflammation leading to the release of pro-inflammatory cytokines and reactive oxygen species that affect neural connectivity and function. Astrocyte dysfunction disrupts the blood-brain-barrier, and may lead to an inflammatory environment in the brain. [2] Cytokines and chemokines are key signalling proteins in ASD neurodevelopment, controlling immunological responses and inflammation. Studies show individuals with ASD often exhibit abnormal levels of cytokines. For example, elevated levels of pro-inflammatory cytokines like IL-6 and TNF-a have been found in the blood and cerebrospinal fluid of people with ASD. These cytokines can influence brain development and function by affecting neuronal connectivity and synaptic plasticity. [3] A Mendelian Randomization analysis results show positive associations between the occurrence of ASD and specific inflammatory markers like sulfotransferase 1A1 and TNF-related apoptosis-inducing ligands while noting inverse relationships with interleukins such as IL-7 and IL-2. Moreover, MMP10, CASP8, and CCL19 were shown to act as late consequences in ASD. [4] Understanding the relationship between inflammatory factors and ASD has significant implications for science and clinical practice. Recent research links ASD to increased pro-inflammatory cytokines and immune dysregulation; increased plasma IL-10 levels in ASD adolescents, predominantly in ASD males [5], with distinct immune patterns in affected children potentially causing neurological and behavioural symptoms. Inflammatory markers profile of cytokine profiles can aid early diagnosis and personalized treatments for ASD, with immunomodulatory therapies promising for treatment. Additionally, prenatal care and early intervention strategies can also prevent ASD. In conclusion, the link between inflammatory variables and autism spectrum disorder (ASD) is significant, with significant literature indicating a link between immunological dysregulation and ASD. Further research is needed to develop targeted treatments and identify inflammatory biomarkers that enhance diagnosis and treatment. Additionally, encouraging understanding and assistance for people with ASD and their families improves community inclusion.